Schiaparelli and the Fusion of Art and Fashion: Clothing as an Art Object - Ferreira, Kamila Premebida; Annes, Luiz Rodolfo (Revista do Colóquio, 2025)
This article analyzes fashion as an aesthetic and cultural form, defining its relationship with art through the influence of Surrealism on the creations of the Schiaparelli brand, problematizing the lack of critical recognition of fashion in the artistic field. Furthermore, it aims to understand how the brand maintains and reinvents its Surrealist heritage. To this end, a qualitative and exploratory bibliographic methodology was used. The results point to fashion as a hybrid artistic language and conclude that it reaffirms its aesthetic power by moving between the catwalk and the museum, consolidating itself as an authentic expression.
Keywords: Art; Fashion; Schiaparelli; Surrealism